Dynamin-related Protein Drp1 Is Required for Mitochondrial Division in Mammalian Cells - Smirnova, Elena (The American Society for Cell Biology, 2001)
Mutations in the human dynamin-related protein Drp1 cause mitochondria to form perinuclear clusters. We show here that these mitochondrial clusters consist of highly interconnected mitochondrial tubules. The increased connectivity between mitochondria indicates that the balance between mitochondrial division and fusion is shifted toward fusion. Such a shift is consistent with a block in mitochondrial division. Immunofluorescence and subcellular fractionation show that endogenous Drp1 is localized to mitochondria, which is also consistent with a role in mitochondrial division. A direct role in mitochondrial division is suggested by time-lapse photography of transfected cells, in which green fluorescent protein fused to Drp1 is concentrated in spots that mark actual mitochondrial division events. We find that purified human Drp1 can self-assemble into multimeric ring-like structures with dimensions similar to those of dynamin multimers. The structural and functional similarities between dynamin and Drp1 suggest that Drp1 wraps around the constriction points of dividing mitochondria, analogous to dynamin collars at the necks of budding vesicles. We conclude that Drp1 contributes to mitochondrial division in mammalian cells.